Structured reporting in fetal magnetic resonance imaging with congenital diaphragmatic hernia - Thater, Greta; Weidner, Anja; Rafat, Neysan; Nowak, Oliver Claudius; Otto, Christiane; Zahn, Katrin; Boettcher, Michael; Schönberg, Stefan; Schaible, Thomas; Weis, Meike (Prenatal diagnosis, 2024)
Objective We aim to provide a template structured report of fetal Magnetic Resonance Imaging in congenital diaphragmatic hernia (CDH) that was locally validated by the CDH study group in Mannheim. Methods A selection of 50 fetal MRIs of patients with an isolated diaphragmatic hernia and associated radiology reports from five different senior radiologists from a single center resulted in a primary structured report, which was put into practice by using dedicated software. A questionnaire survey of the interdisciplinary CDH study group Mannheim was used to adapt the report to the clinical requirements. Results There was a huge variability in how deep the free text reports go into detail. The side of the hernia was named in 94% of cases. In 58%, both the lung volume and the total lung volume were reported. A comparison with the expected lung volume was reported in 66% of cases. Additional findings, such as herniated organs, were reported in 96% of cases. Overall satisfaction with the newly established structured report was high within the CDH study group with a mean of 4.7. Conclusions The use of the structured report of this study can optimize the interdisciplinary dialog, the standardization of report content, increase report completeness and improve quality.
Online veröffentlicht: 26. Mai 2024
Gesehen am 03.02.2025